The impact of neoliberalism on academics and students in higher education: A call to adopt alternative philosophies - Desierto, Anibeth; De Maio, Carmela (Journal of Academic Language and Learning, 2020)
In adopting neoliberalism, higher education institutions may view students as consumers rather than learners. This sits uncomfortably with humanistic and critical teaching philosophies which view learning as contextualised within a caring environment. In this environment, students become effective, lifelong learners who can contribute to a better society. However, although humanistic educational philosophies, such as Vygotsky’s social-constructivist approach and Freire’s pedagogy of care appear to resonate with academics and students, we argue that neoliberalism and its associated issues are predominant in higher education. This paper discusses the effects of neoliberalism in higher education. It outlines the financial, economic and psychological toll on both students and academics in a climate of increasing casualisation of the workforce and loss of employment; factors which not only impact on students and academics but also on the viability of universities themselves. Finally, we suggest that higher education institutions and universities emphasise alternative philosophies that nurture and support higher education students and their learning.